Anxiety and depression in higher education students: comparison between measurement instruments: Comparison between measurement instruments - Minghelli, Beatriz (Cadernos Brasileiros de Saúde Mental/Brazilian Journal of Mental Health, 2022)
BACKGROUND: There are several measurement instruments to evaluate anxiety and depressive with differences in filling time and number of questions. This study aimed to verify the correlation between differents measurement instruments in the evaluation of anxiety and depression symptoms in high education students. METHODS: The sample comprised 148 students, being 108 (73%) female, aged between 18 to 54 years old (26.61±7.69). The measurement instruments included Beck Anxiety Inventory (BAI), Beck Depression Inventory (BDI) and Hospital Anxiety and Depression scale, that evaluated both anxiety (HADS-A) and depression (HADS-D). RESULTS: The Kappa value of 0.5 revealed a moderate strength of agreement between HADS-A and BAI. The majority (65.9%) classified with anxiety by HADS-A was also classified as anxiety by BAI. For the depression concordance, the Kappa value of 0.61 revealed a good strength of agreement. 50% of students who were classified with depression with the HADS-D and also classified as depression by BDI. Spearman’s Rho value was 1 for both anxiety and depression quantitative variables, which means a perfect positive correlation between these variables. Women having 2.46 (CI: 0.99-6.09; p=0.052) more chances of being anxious compared to men using both anxiety scales (BAI and HADS-A) and older students were 6.52 (CI: 13.8-30.92; p=0.018) more probabilities to develop symptoms of depression than younger ones, according to HADS-D. CONCLUSIONS: Data in this study revealed a good correlation between the measurement instruments that assess symptoms of anxiety and depression, suggesting that the researcher can choose the instrument that best suits the logistics of his/her research.